2009
DOI: 10.1007/s12011-009-8421-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Serum Ca and Mg Levels with Mental Health in Adult Women Without Psychiatric Disorders

Abstract: Several lines of evidence from previous studies suggest that Calcium (Ca) and Magnesium (Mg) may be involved in intracellular and interneuronal processes associated with affective disorders. However, there have been inconsistent results on the effect of Ca and Mg on depressive mood disorder. This cross-sectional study was conducted to determine whether serum Ca and Mg levels, as well as serum Ca/Mg ratio, are associated with mental health in relatively healthy, adult women without psychiatric disorders. One hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 29 publications
2
22
0
5
Order By: Relevance
“…En el presente estudio se encontr贸 que entre los adultos con presencia de desnutrici贸n la mayor铆a ten铆an sintomatolog铆a depresiva. Una posible relaci贸n inversa puede explicar los resultados, donde un estado nutricional inadecuado, espec铆ficamente en la etapa de vejez, incrementa la vulnerabilidad ante enfermedades mentales como la depresi贸n 32 . En este sentido, la literatura refiere que la presencia de riesgo nutricional en estadios avanzados de edad desencadena mayor sintomatolog铆a depresiva 33 .…”
Section: G茅nerounclassified
“…En el presente estudio se encontr贸 que entre los adultos con presencia de desnutrici贸n la mayor铆a ten铆an sintomatolog铆a depresiva. Una posible relaci贸n inversa puede explicar los resultados, donde un estado nutricional inadecuado, espec铆ficamente en la etapa de vejez, incrementa la vulnerabilidad ante enfermedades mentales como la depresi贸n 32 . En este sentido, la literatura refiere que la presencia de riesgo nutricional en estadios avanzados de edad desencadena mayor sintomatolog铆a depresiva 33 .…”
Section: G茅nerounclassified
“…14 Recently, relatively high levels of depressive mood, anxiety, and stress perception were found to be associated with lower levels of serum Mg in healthy adult women who had no history of psychiatric disorders. 15 The relationship of Mg levels with depression severity, specific psychopathological dimensions, and the therapeutic course of depression has also been investigated, though consistent results have not yet been obtained. Widmer et al 16,17 reported that plasma and erythrocyte Mg levels were higher in patients with mood disorders compared to normal subjects, both before and after treatment, and pointed out that this is a disease-specific manifestation.…”
Section: Introductionmentioning
confidence: 99%
“…18 An association between Mg and anhedonic features, which typically characterize major depression, has been suggested by a recent study in which Mg's (MgCl 2 0.2 mM/kg/day) influence on the reward system was tested using conditioned place preference in rats and Mg has been shown to moderately stimulate the reward system. 15 A relation between Mg and a therapeutic potential in affective disorders has been noted as early as 1921: hypodermically administered Mg sulphate caused 50 patients having agitated depression to relax and sleep from 4 to 6 hours. 19 In a randomized clinical trial, oral Mg supplementation was as effective as imipramine in treating depressed elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…They found that total plasma magnesium levels were lower among patients, but no difference in levels of ionized magnesium (12). Jung et al assessed serum magnesium levels in 112 healthy adult women without psychiatric disorders and observed that women in the lowest tertile of serum magnesium levels had a higher risk of developing depressive mood disorder (13).…”
Section: Discussionmentioning
confidence: 99%